Fundamental parenchyma cells are involved in Na+ and Cl– removal ability in rice leaf sheath - Neang, Sarin; de Ocampo, Marjorie; Egdane, James A.; Platten, John D.; Ismail, Abdelbagi M.; Skoulding, Nicola S.; Kano-Nakata, Mana; Yamauchi, Akira; Mitsuya, Shiro (Commonwealth Scientific and Industrial Research Organisation, 2019)
Salt sensitivity in rice plants is associated with the accumulated amount of Na+ and Cl– in shoots and, more significantly, in photosynthetic tissues. Therefore, salt removal ability at the leaf sheath level is an important mechanism of salt tolerance. In the present study we attempted to determine whether rice leaf sheaths excluded Cl– as well as Na+, and to identify the tissues that were involved in the removal ability of both ions. In two rice genotypes, salt-tolerant FL478 and -sensitive IR29, leaf sheaths excluded Na+ and Cl– under NaCl treatment as estimated using their sheath:blade ratios. The sheath:blade ratio of Na+ but not of Cl–, was increased by NaCl treatment. Under NaCl treatment, Na+ concentration was higher in the basal leaf sheath, whereas Cl– concentration was higher in the middle and tip parts. At the tissue level, fundamental parenchyma cells of leaf sheaths retained the highest amounts of Na and Cl when treated with high amount of NaCl. These results imply that the leaf sheath potentially functions to remove excess Na+ and Cl– from xylem vessels in different locations along the axis, with the fundamental parenchyma cells of leaf sheaths being involved in over-accumulation of both Na+ and Cl–.